Akselerasi SDG 4 melalui Masterclass Beasiswa Pertamina Foundation di Universitas Islam Riau - Ratu Ganisa Auliana; Shandy Kurniadi (Yumary: Jurnal Pengabdian kepada Masyarakat, 2026)
Purpose: This Community Service (PKM) program aims to accelerate SDG 4 (Quality Education) by assisting Universitas Islam Riau students in preparing comprehensive scholarship application packages (essays and motivation letters) for the Pertamina Foundation scholarship. Method: The implementation method consists of four structured stages: preparation, intensive interactive mentoring, final evaluation, and achievement metrics data analysis. Results/findings: The intensive mentoring approach successfully improved participants' technical readiness. This is statistically indicated by a 9.99% increase in average pre-test to post-test scores (from 60.76% to 70.75%), backed by a 100% participant satisfaction rate on a Likert-scale survey. Conclusions: Through a responsive, two-way coaching approach, this program has demonstrably succeeded in enhancing the conceptual understanding, technical readiness, and learner autonomy of students at the Universitas Islam Riau in preparing scholarship application documents. Limitations: The scope of this study is constrained by technical network asymmetry, limited mentoring duration, and short-term evaluation metrics. Additionally, the study does not capture long-term sustainability effects, as post-intervention outcomes beyond the observation period were not assessed. Contributions: This program contributes to Academic Capacity Building and institutional SDG 4 acceleration by providing a highly effective, replicable intervention model for student financial attainment.